Preparation of sodium vanadium phosphate positive electrode material with high electrochemical performance
Through sol-gel method and muffle furnace treatment method, a sodium vanadium phosphate positive electrode material with high electronic conductivity and good cycling performance was prepared, which solved the problem of poor charging and discharging performance of existing materials at high currents, and realized the Higher electrochemical properties and simplified process.
Patent Information
- Application Number
- CN202411397345.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2024-12-20
AI Technical Summary
The existing sodium vanadium phosphate positive electrode materials have low electronic conductivity, resulting in poor charging and discharging performance at high currents and complex preparation process, which affects the performance of electrochemical performance.
The sol-gel method is used to react citric acid with the raw materials in an appropriate stoichiometric ratio to prepare NVP/c precursor, and the carbon layer is modified through a muffle furnace to improve the charge transfer performance, while removing excess carbon and maintaining high electricity. Chemical activity.
It improves the rate performance and reversible capacity of sodium ion batteries, enhances cycling performance and electrochemical activity, and significantly improves the electrochemical performance of the materials.
Smart Images

Figure CN119170751A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sodium vanadium phosphate preparation, and in particular to a carbon-coated NASICON type sodium vanadium phosphate positive electrode material and a preparation method thereof. Background Art
[0002] With the introduction of the dual-carbon strategy, clean energy technology continues to develop and traditional energy is gradually replaced. Large-scale energy storage is an essential component of the future development of clean energy. However, as the most widely used energy storage system, lithium-ion batteries (LIBs) have disadvantages such as high cost, poor safety, and a narrow applicable temperature range. Sodium-ion batteries (SIBs) are considered to be a promising energy storage material because they are cheap and have the same energy storage principle as lithium-ion batteries. The conversion and storage of energy has become a key issue related to our daily lives.
[0003] Among various cathode materials, polyanions have attracted extensive attention due to their smaller structural changes than layered materials during (de)sodiumization and higher working potential than Prussian blue analogs. In the trigonal Na3V2(PO4)3 crystal structure, the VO6 octahedron corners are connected with the PO4 tetrahedron corners to form a three-dimensional skeleton. + It can diffuse along the x, y, and z axes, so the ion diffusion coefficient is high, making it an ideal candidate material for fast-charging sodium-ion batteries. However, due to the strong force of the PO and VO bonds, the material has a small number of free electrons, low electronic conductivity, and poor rate performance at high currents. In order to improve the low electronic conductivity of NVP and further improve its electrochemical performance in practical applications, many scholars have proposed many modification methods, including heteroatom doping and carbon material composites.
[0004] In the prior art, a liquid phase reaction method is often used to first prepare a precursor, and then calcine it under an inert atmosphere to obtain a target product. For example, CN 202111300358.2 provides a sodium vanadium phosphate carbon composite material and its preparation method and application. The synthesis process is complex and the process is cumbersome. The conductivity of the obtained sodium vanadium phosphate carbon composite material is still poor, which affects its electrochemical performance. Summary of the invention
[0005] In view of the above defects and improvement needs of the existing NVP preparation technology, the present invention uses a sol-gel method to react citric acid and raw materials in a suitable stoichiometric ratio to prepare an NVP / C precursor, and then obtains the positive electrode material of NVP / C through treatment in a muffle furnace. Among them, citric acid serves as both a reducing agent and a complexing agent. Due to the addition of citric acid, the charge transfer of NVP / C is affected, and the rate performance of the battery is improved. At the same time, the muffle furnace treatment modifies the carbon layer, while improving the charge transfer, removing excess carbon without sacrificing its high electrochemical activity. The treated carbon material has good reversible sodium ion deintercalation performance, high reversible capacity and good cycle performance.
[0006] First, citric acid and raw materials were dissolved in deionized water according to the stoichiometric ratio and stirred in a water bath until the solution turned blue and evaporated into a gel.
[0007] Secondly, the gel obtained above is placed in a vacuum drying oven for drying, and the obtained solid material is ground into powder.
[0008] Next, the powder obtained above is placed in a high temperature carrier and sintered at a fixed sintering temperature, sintering time and heating rate in a certain atmosphere to obtain NVP / C powder; Afterwards, the powder obtained above is placed in a muffle furnace and treated at a fixed calcination temperature, calcination time and heating rate; Finally, electrodes were prepared, batteries were assembled, and electrochemical performance was tested. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 The X-ray diffraction patterns (XRD) of the cathode materials before and after carbon removal at different holding times; Figure 2 The scanning electron microscope images (SEM) of the sodium vanadium phosphate cathode material before and after decarbonization and sintering for 5 hours; Figure 3 The cyclic voltammetry (CV) curves of the sodium vanadium phosphate cathode material at 2.5-4 V before and after decarbonization and sintering for 5 hours; Figure 4 The charge-discharge specific capacity curves of the sodium vanadium phosphate cathode material sintered at a rate of 0.1C for the first three cycles without decarbonization and after decarbonization and sintering for 5 hours; Figure 5 The battery was assembled with sodium vanadium phosphate cathode materials without carbon removal and sintered at 5 h after carbon removal at 2C (1C = 117 mA g -1 ) under long cycle performance diagram; Figure 6 This is the rate performance diagram of sodium vanadium phosphate positive electrode material sintered at 5 hours without decarbonization and after decarbonization. DETAILED DESCRIPTION
[0010] In order to make the purpose, technical solution and advantages of the present invention more clearly presented, the embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. Examples of these preferred embodiments are illustrated in the accompanying drawings. The embodiments of the present invention shown in the accompanying drawings and described according to the accompanying drawings are merely exemplary, and the present invention is not limited to these embodiments.
[0011] As a positive electrode material for sodium ion batteries, sodium vanadium phosphate is one of the candidate materials for positive electrode materials for sodium ion batteries due to its high voltage platform, stable three-dimensional structure, good ionic conductivity and good thermal stability. The embodiment of the present invention conducts experimental research on sodium vanadium phosphate materials to obtain a sodium vanadium phosphate positive electrode material for sodium ion batteries with excellent electrochemical performance.
[0012] The embodiment of the present invention provides a method for preparing the sodium vanadium phosphate positive electrode material as described above, the preparation method comprising the steps of: S1, dissolving ammonium metavanadate in deionized water, adding citric acid solution dropwise, stirring at a suitable temperature until the solution changes from yellow to blue. Then adding sodium carbonate and diammonium dihydrogen phosphate, and continuing to stir until it becomes a gel; S2, drying the gel obtained in S1 in a vacuum drying oven, and grinding the obtained solid until it is in powder form; S3, placing the powder obtained in S2 in a tubular furnace, introducing an inert gas, and using a suitable heating rate to a certain temperature, keeping the temperature at this temperature for a certain time for primary sintering, and then using a suitable heating rate to a certain temperature, keeping the temperature at this temperature for a certain time for secondary sintering, and cooling to room temperature with the furnace. In the preferred embodiment, the mixed inert gas during high-temperature sintering is N2 or Ar, the primary sintering temperature is 200-400℃, the sintering time is 3-5 h, and the heating rate is 1-10℃ / min. The secondary sintering temperature is 600-800℃, the sintering time is 4-6 h, and the heating rate is 1-10℃ / min; S4, placing the powder sintered in S3 in a muffle furnace, and treating it at a fixed sintering temperature, sintering time and heating rate to obtain a sintered active material powder. In the preferred embodiment, the sintering temperature is 300-500°C, the sintering time is 1-10min, and the heating rate is 1-10°C / min; The present invention also provides a sodium ion battery, which comprises an electrode prepared from the sodium vanadium phosphate positive electrode material as described above.
[0013] Example 1: Sintering time 4h treatment This embodiment provides a sodium vanadium phosphate positive electrode material, which is prepared by sol-gel plus muffle furnace. In this embodiment, the primary sintering temperature for preparing the sodium vanadium phosphate positive electrode material is 350 ° C, and the holding time is 4 h; the secondary sintering temperature is 800 ° C, and the holding time is 4 h; the raw material ratio used is 2:3:2:3 (citric acid: Na:V:P); the heating rate of the two stages is 5 ° C / min, and the inert atmosphere is N2.
[0014] The present invention is a method for preparing a 4h sintered sodium vanadium phosphate positive electrode material, and the specific steps are as follows: Weigh 0.468g of NH4VO3 and dissolve it in 50ml of deionized water, add citric acid solution (0.897g dissolved in 25ml of deionized water) dropwise, put it in a water bath at 80℃ and stir until the solution changes from yellow to blue. Then add 3.18g of Na2CO3 and 0.69 of NH4H2PO4 and continue stirring until it becomes a gel.
[0015] The gel obtained above was placed in a vacuum drying oven and dried at 120°C to obtain a solid, which was then ground into powder. The powder was placed in a tubular furnace, nitrogen was introduced, and the temperature was kept at 350°C for 4 hours, and then the temperature was increased to 800°C for 4 hours at a heating rate of 5°C / min. Finally, NVP / C powder was obtained, and the powder was placed in a muffle furnace and kept at 400°C for 5 minutes at a heating rate of 5°C / min.
[0016] The NVP / C powder obtained above was used as the active material, and the conductive material and binder were added to the solvent in a suitable proportion. After stirring for 5-6 hours, the positive electrode slurry was obtained, and it was coated on the aluminum foil with a certain thickness. It was vacuum dried in a vacuum oven for 12 hours, and then the positive electrode sheet cut into a diameter of 12 mm was taken out; the sodium ion battery was assembled in a glove box, and the electrochemical performance test was carried out.
[0017] Example 2: Sintering time 5h treatment The difference between this embodiment and embodiment 1 is that the final sintering time is 5 hours.
[0018] The present invention is described in the embodiment of the present invention is a method for preparing a 5h sintered sodium vanadium phosphate positive electrode material, and the specific steps are as follows: Weigh 0.468g of NH4VO3 and dissolve it in 50ml of deionized water, add citric acid solution (0.897g dissolved in 25ml of deionized water) dropwise, put it in a water bath at 80℃ and stir until the solution changes from yellow to blue. Then add 3.18g of Na2CO3 and 0.69 of NH4H2PO4 and continue stirring until it becomes a gel.
[0019] The gel obtained above was placed in a vacuum drying oven and dried at 120°C to obtain a solid, which was then ground into powder. The powder was placed in a tubular furnace, nitrogen was introduced, and the temperature was kept at 350°C for 4 hours, and then the temperature was raised to 800°C and kept for 5 hours at a heating rate of 5°C / min. Finally, NVP / C powder was obtained, and a portion was taken as the original control group. The remaining powder was placed in a muffle furnace and kept at 400°C for 5 minutes at a heating rate of 5°C / min. XRD tests were performed on the original group and several materials treated in muffle furnaces with different sintering times, such as Figure 1 The characteristic peaks of NVP can be clearly seen in the figure. At the same time, it can be clearly observed that the peak value is enhanced after the muffle furnace decarbonization treatment, and the degree of crystallization is higher. As the insulation time increases, the peak value of the material gradually increases. In addition, the SEM morphology of the original group and the muffle furnace decarbonization treatment materials is characterized, as shown in Figure 2. Figure 2 There are some holes in both materials. The rich pore structure can make the electrode better wetted by the electrolyte and shorten the diffusion path of sodium ions. At the same time, the electrochemical activity of the battery material is improved after decarbonization in the muffle furnace.
[0020] The above-obtained doped bamboo charcoal powder was used as an active material, and a solvent was added with a conductive material and a binder in a suitable proportion. After stirring for 5-6 hours, a negative electrode slurry was obtained, and it was coated on a copper foil with a certain thickness. The negative electrode sheet was vacuum dried for 10 hours in a vacuum drying phase, and then the negative electrode sheet cut into a diameter of 12 mm was taken out; the sodium ion battery was assembled in a glove box, and the electrochemical performance test was carried out.
[0021] The NVP / C powder obtained above was used as the active material, and the conductive material and binder were added to the solvent in a suitable proportion. After stirring for 5-6 hours, the positive electrode slurry was obtained, and it was coated on the aluminum foil with a certain thickness. It was vacuum dried in a vacuum oven for 12 hours, and then the positive electrode sheet cut into a diameter of 12 mm was taken out; the sodium ion battery was assembled in a glove box, and the electrochemical performance test was carried out. Figure 3 In the cyclic voltammetry test (CV), the sample decarbonized for 5 h showed a higher peak current response and better repeatability in the voltage range of 2.5-4 V, while the original material showed obvious attenuation with the cycle; indicating that after decarbonization, the sodium vanadium phosphate material showed higher reversible capacity and better cycle reversibility. Figure 4 The charge-discharge capacity of the original material and the material treated by muffle furnace decarbonization and heat preservation for 5 hours in the first three cycles at a rate of 0.1C. The charge capacity of the material sintered after decarbonization for 5 hours can reach 105.3 mAh g -1 , and a first coulombic efficiency of 98.93%. In addition, compared with the original material, the decarbonized material avoids the obvious voltage drop problem. Figure 5 This is a long cycle test in the voltage range of 2.5-4 V and at a rate of 5C. The treated material showed higher capacity and capacity retention after 300 cycles. Figure 6 The figure shows the rate test of the two materials. No matter at the low rate of 0.1C or the high rate of 5C, the sodium vanadium phosphate positive material treated by muffle furnace decarbonization and heat preservation for 5 hours shows a higher discharge specific capacity, and can still maintain the original performance when it returns to the rate of 0.1C. It can be proved from many aspects that the sodium vanadium phosphate positive material treated by muffle furnace decarbonization and heat preservation for 5 hours shows the best electrochemical performance.
[0022] Example 3: Sintering time 6h treatment The difference between this embodiment and embodiment 1 is that the final sintering time is 6 hours.
[0023] The present invention is a method for preparing a 6h sintered sodium vanadium phosphate positive electrode material, and the specific steps are as follows: Weigh 0.468g of NH4VO3 and dissolve it in 50ml of deionized water, add citric acid solution (0.897g dissolved in 25ml of deionized water) dropwise, put it in a water bath at 80℃ and stir until the solution changes from yellow to blue. Then add 3.18g of Na2CO3 and 0.69 of NH4H2PO4 and continue stirring until it becomes a gel.
[0024] The gel obtained above was placed in a vacuum drying oven and dried at 120°C to obtain a solid, which was then ground into powder. The powder was placed in a tubular furnace, nitrogen was introduced, and the temperature was kept at 350°C for 4 hours, and then the temperature was increased to 800°C for 6 hours at a heating rate of 5°C / min. Finally, NVP / C powder was obtained, and the powder was placed in a muffle furnace and kept at 400°C for 5 minutes at a heating rate of 5°C / min.
[0025] The NVP / C powder obtained above was used as the active material, and the conductive material and binder were added to the solvent in a suitable proportion. After stirring for 5-6 hours, the positive electrode slurry was obtained, and it was coated on the aluminum foil with a certain thickness. It was vacuum dried in a vacuum oven for 12 hours, and then the positive electrode sheet cut into a diameter of 12 mm was taken out; the sodium ion battery was assembled in a glove box, and the electrochemical performance test was carried out.
Claims
1. A method for preparing a sodium vanadium phosphate carbon composite material, characterized in that: Includes steps: (1) Dissolve the vanadium source in deionized water, add the carbon source, and stir at 80°C until the solution changes from yellow to blue. Then add the sodium source and phosphorus source, and continue stirring at 80°C until it becomes a gel; (2) placing the obtained gel in a vacuum drying oven, drying it, and grinding the obtained solid until it is in powder form; (3) placing the obtained powder in a tube furnace and introducing an inert gas, and calcining under the protection of the inert atmosphere to obtain the sodium vanadium phosphate carbon composite material, wherein the calcination is a two-step calcination; (4) The sintered powder is placed in a muffle furnace and treated at a fixed calcination temperature, calcination time and heating rate to obtain a sintered active material powder.
2. The method for preparing the sodium vanadium phosphate carbon composite material according to claim 1, characterized in that: The vanadium source is ammonium vanadate, the sodium source is sodium carbonate, the phosphorus source is ammonium dihydrogen phosphate, and the carbon source is citric acid, which also serves as a complexing agent.
3. The method for preparing the sodium vanadium phosphate carbon composite according to claim 1, characterized in that: The ratio of the raw materials used is 3:2:3 (Na:V:P), and the ratio of the vanadium source to the carbon source is 1:1-6:
7.
4. The method for preparing the sodium vanadium phosphate carbon composite according to claim 1, characterized in that: The inert gas is N2 or Ar, the primary sintering temperature is 200-400°C, the sintering time is 3-5 h, and the heating rate is 1-10°C / min. The secondary sintering temperature is 600-800°C, the sintering time is 4-6 h, and the heating rate is 1-10°C / min.
5. The method for preparing the sodium vanadium phosphate carbon composite according to claim 1, characterized in that: The muffle furnace sintering temperature is 300-500° C., the sintering time is 1-10 min, and the heating rate is 1-10° C. / min.
6. A sodium vanadium phosphate carbon composite material for a positive electrode of a sodium ion battery prepared by the preparation method according to any one of claims 1 to 5.
Citation Information
Patent Citations
Sodium vanadium phosphate carbon composite material as well as preparation method and application thereof
CN113735092A
